UPAYA PENGEMBANGAN USAHA MIKRO KECIL DAN MENENGAH (UMKM) HANDYCRAFT KAYU JATI DI DUSUN BANDAR DESA BATOKAN KECAMATAN KASIMAN KABUPATEN BOJONEGORO - Daroin, Ana Dhaoud; Joyoatmojo, Soetarno; M.Bus, Susilaningsih (Jurnal Pendidikan Insan Mandiri, 2015)
The objectives of this research are to describe: (1) the development efforts of micro-, small-, and medium-scale enterprises of teakwood handicraft in Bandar sub-village, Batokan village, Kasiman sub-district, Bojonegoro regency through the aspect of production to increase the community income; and (2) the development efforts of micro-, small-, and medium-scale enterprises of teakwood handicraft in Bandar sub-village, Batokan village, Kasiman sub-district, Bojonegoro regency through the aspect of marketing to increase the community income. This research used the descriptive research method with the qualitative phenomonology approach.The samples of research were taken by using the purposive and snowball sampling techniques.The data of research were gathered through in-depth interview, observation, and documentation. They were validated by using source triangulation and method triangulation. The data were analyzed by using the interactive model of analysis comprising four components, namely: data gathering, data reduction, data display, and conclusion drawing. The results of research show that there are six development efforts of micro-, small-, and medium-scale enterprises of teakwood handicraft in Bandar sub-village, Batokan village, Kasiman sub-district, Bojonegoro. This research conclude that: (1) In term of production aspect, the efforts include granting production aids by the government and conducting product innovations; and (2) In term of marketing, they include holding exhibitions, conducting comparative studies, conducting wood fair activities, and marketing the products through internet. The result of observation shows that the highest turnover average achieved by the micro-, small-, and medium-enterprises took place in 2013, that is, 4.01%, whereas the lowest turnover average persisted in 2011, that is, 0.81%. Therefore, a conclusion can be drawn that the most strategic development efforts were applied in 2013. The efforts included product innovations, exhibitions, wood fair, and product marketing through internet.Keywords:     Qualitative phenomonology approach, purposive sampling techniques,   snowball sampling techniques,  production, and marketing